فاعلية برنامج قائم على روبوتات الدردشة التفاعلية Chatbots لتنمية بعض مهارات الفهرسة المقروءة آليا مارك 21 لدى طلاب المكتبات وتكنولوجيا التعليم بجامعة الأزهر - هندي، أسامة محسن محمود (جامعة بني سويف - كلية الآداب, 2022)
استهدف البحث التعرف على دور برنامج قائم على روبوتات الدردشة (Chatbots) في تنمية الجوانب المعرفية لدى طلاب الفرقة الأولى بالمكتبات والمعلومات وتكنولوجيا التعليم بتربية الأزهر بالقاهرة، مستخدما أداة الاختبار المعرفي وبطاقة تقييم منتج، وبعد تقنين الأدوات وحساب صدقها وثباتها، طبقت على عينة استطلاعية من عشر طلاب تم اختيارهم بشكل عمدي، واستخدم الباحث المنهج شبه التجريبي Quasi-Experimental، كما استخدم التصميم التجريبي ذو المجموعتين المتكافئتين التجريبية والضابطة بطريقة القياس القبلي والبعدي. وبعد حساب درجات طلاب المجموعتين، ومعالجتها إحصائيا، جاءت النتائج بوجود فروق دالة إحصائيا عند مستوى ≥ 0.05بين درجات أفراد المجموعتين التجريبية والضابطة، لصالح المجموعة التجريبية في التطبيقين القبلي والبعدي للاختبار المعرفي وبطاقة تقييم المنتج؛ مما يؤكد فاعلية البرنامج القائم على روبوت الدردشة للذكاء الاصطناعي في تنمية الجوانب المعرفية والمهارية للطلاب، كما أن النتائج التي استخرجت من ملف (log) في موقع روبوت الدردشة التفاعلية Chatbots بعد معالجتها أظهرت إقبال الطلاب في المجموعة التجريبية على المحادثة مع الروبوت للسؤال عن معلومات محددة. وبناء عليه فإن معدل استخدام الطلاب للنظام كمساعد في عملية التعلم أسهم في تحسين نواتج التعلم، وقد اقترح الباحث بعض البحوث المستقبلية وثيقة الصلة بموضوع البحث. The research aimed to identify the role of a program based on chatbots in developing the cognitive aspects of first year students in libraries, information and educational technology in Al-Azhar Education in Cairo, using the cognitive test tool and a product evaluation card, and after codifying the tools and calculating their validity and stability, it was applied to a pilot sample of ten Students were deliberately selected, and the researcher used the quasi-experimental method, and the experimental design with two equal groups, experimental and control, was used in the way of pre- and post-measurement. After calculating the scores of the students of the two groups, and treating them statistically, the results came with a statistically significant difference at the level of ≥ 0.05 between the scores of the members of the experimental and control groups, in favor of the experimental group in the pre and post applications of the cognitive test and the product evaluation card. This confirms the effectiveness of the program based on the chatbot for artificial intelligence in developing the cognitive and skill aspects of students, and the results that were extracted from the (log) file on the Chatbots website after processing it showed that the students in the experimental group had a conversation with the robot to ask for specific information. Accordingly, the rate at which students use the system as an aid in the learning process has contributed to improving learning outcomes, and the researcher has suggested some future research closely related to the topic of the research.
Keywords: التكنولوجيا الرقمية -- روبوتات المحادثة -- مهارات الفهرسة الآلية -- طلبة المكتبات -- تكنولوجيا التعليم -- جامعة الأزهر